May Measurement Month 2019: an analysis of blood pressure screening results from the Democratic Republic of the Congo. (20th May 2021) - M'Buyamba-Kabangu, Jean-René; Katamba, Fortunat K; Ntambwe, Mireille L; Ngoyi, Georges N; Tshiswaka, Trésor M; Bayauli, Pascal M; Lubenga, Yves N; Kazadi, Serge M; Beaney, Thomas; Xia, Xin; Poulter, Neil R; Buila, Nathan B
Abstract: Hypertension, the foremost cause of global morbi-mortality, is linked with a high mortality from numerous cardiovascular endpoints. The May Measurement Month (MMM) campaign is an annual initiative of the International Society of Hypertension (ISH) to collect information on blood pressure (BP) and other risk factors for cardiovascular disease (CVD) in adults. MMM2019 in the Democratic Republic of the Congo (DRC) was an opportunistic cross-sectional survey of volunteers aged ≥18 years that took place in Kinshasa and Mbuji-Mayi after the training of observers to familiarize with the ISH ad hoc methods. We screened 29 857 individuals (mean age: 40 years; 40% female). Hypertension was present in 7624 (25.5%) individuals. Of them, 2520 (33.1%) were aware, 1768 (23.2%) on treatment with 910 (51.5%) controlled BP (systolic BP <140 mmHg and/or diastolic BP <90 mmHg). Of all hypertensives screened, 11.9% had controlled BP. Of all respondents, 16.7% had participated in MMM18 and 60.5% did not have their BP verified during the last year. Fasting, pregnancy, and underweight status were linked with lower BP levels whilst smoking, drinking, antihypertensive medication, previous stroke, diabetes as well as being overweight/obese were associated with higher BP levels. Our results reflect the high rate of hypertension in the DRC with low levels of awareness, treatment, and control. A nationally representative sample is required to establish the nationwide hypertension prevalence.